EDUKASI MENENUN KEPADA ANAK SEKOLAH DASAR DI DUSUN BATANG PALLI, DESA SA’DAN TIROALLO - Lewi Nataniel Bora; Lidya Rante Bua (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2022)
Toraja woven cloth is the work of the Toraja people. The weaving process can be lost if children are not given education about woven fabrics and how to make them. Their knowledge of how to make woven fabrics can inspire love and help the family’s economy. The woven fabrics produced can be sold to the market or people in need. Based on the observations made, some children in Batang Palli hamlet know how to weave, but they do not do the weaving process. Others don’t know how to weave, and they only know it as a parent’s job. This is what encourages education for the children who are there. The method used in writing this article is qualitative with an ethnographic approach. From the education process, it can be seen that the children in Batang Palli hamlet are interested in weaving, only they do not have a good understanding of the cultural and economic values of woven fabrics. This activity is expected to increase the interest of children in the Batang Palli hamlet to preserve woven fabrics.